Study protocol: prevalence of low energy availability and its relation to health and performance among female football players - Rosenvinge, J. H.; Smavik Dasa, M.; Kristoffersen, M.; Pettersen, G.; Sundgot-Borgen, J.; Sagen, J. V.; Friborg, O. (BMJ Open Sport & Exercise Medicine, 2022)
Enduring low energy availability (LEA) is associated with several potentially serious physiological and mental conditions. LEA has been found highly prevalent among female elite athletes within endurance sports, thus hampering athletes` health and performance. The prevalence and the underpinning risk factors of LEA among female elite football players are less studied. One reason is that the existing self-report measures and technological devices to monitor energy intake and expenditure are inadequately adapted to capture the nature of the physical activity and energy expenditure among football players and are thus inaccurate.